Peran Administrasi Pendidikan Dalam Meningkatkan Mutu Pendidikan Karakter di Madrasah Ibtidaiyah - Siregar, Hidayati; Erlangga, Rizen; Dalila, Sastri; Harahap, Kholila; Balqis, Ratika (Prodi PGMI STIT Al-Ittihadiyah Labuhanbatu Utara, 2025)
This study aims to analyze the role of educational administration in improving the quality of character education in Islamic elementary schools through a library research approach. This study focuses on theoretical reviews, previous research results, and relevant scientific literature regarding educational administration and character education in Islamic elementary schools. Data were collected through a search of scientific journals, books, and academic publications published in the last ten years, then analyzed descriptively and qualitatively to find the relationship between the educational administration system and the effectiveness of character education. The results show that good educational administration—including planning, organizing, implementing, and evaluating—has a significant influence on the success of character education programs. Structured administration enables Islamic elementary schools to create a conducive learning climate, integrate character values ​​into learning activities, and increase the participation of teachers, students, and the community. Previous research also shows that collaboration between all school members and the application of information technology in administration can strengthen the management of character education. Therefore, it can be concluded that educational administration is not merely a bureaucratic activity, but a strategic foundation for building a madrasah culture of character, discipline, and noble morals. The results of this study are expected to serve as a reference for policymakers, madrasah principals, and educators in optimizing educational administration to achieve superior and sustainable character education.